Impact of contract farming on yield, costs and profitability in low‐value crop: Evidence from a low‐income country - Mishra, Ashok K.; Kumar, Anjani; Joshi, Pramod Kumar; D'Souza, Alwin (Wiley, 2018)
Lentils, a low‐value and highly nutritious crop, are Nepal's largest pulse cash crop. However, the majority of the nation's smallholders produce lentils on very small plots of land. The large gap in lentil yields between Nepal and other lentil‐producing countries underscores the importance of improving yields and income of smallholders. When it comes to the financial viability of small farms, particularly in developing countries, and globalisation, contract farming (CF) may prove useful in achieving efficiency and profitability in smallholder lentil farms in Nepal. This study employs the propensity score matching approach to examine the effects of the adoption of CF on yields, profitability and costs of smallholder lentil farms in Nepal. Findings from this study reveal that contrary to popular belief, CF adoption by lentil producers in Nepal has a positive and significant effect on per‐hectare revenues, profits and yield and a negative impact on variable and transportation costs. The study finds that only very smallholder lentil farms (0.01‐0.05 ha) benefit from CF.